EFICIÊNCIA FISIOLÓGICA DE EXPRESSÃO DE CARACTERES DA PANÍCULA DE AVEIA: EFEITOS GENÉTICOS E AMBIENTAIS - Silva, José A. G. D.; Krüger, Cleusa A. M. B.; Sartori, César O.; Gaviraghi, Juliano; Pinto, Fernando B.; Silva, Adair J. D. (Salão do Conhecimento, 2013)
Resumo